F28 The contribution of attentional defects on motor, functional, and psychopathological dysfunctions in huntington's disease. (September 2018) - Lucia, Natascia De; Roca, Alessandro; Peluso, Silvio; Bruzzese, Dario; Bilo, Leonilda; Maio, Luigi Di; Michele, Giuseppe De; Salvatore, Elena
Abstract : Background: Attentional difficulties are very frequent among patients affected by Huntington's disease (HD), a rare autosomal dominant neurodegenerative disorder. Aims: In the present study we aimed to assess whether and how different types of attention are associated to CAG size, disease duration, motor disorders, functional dysfunction and psychopathological signs in symptomatic HD patients. Methods: We recruited a prospective sample of 22 symptomatic HD patients and 22 healthy controls who underwent a clinical, neuropsychological and psychopathological assessment, and an evaluation of the sustained, selective and divided attention. Results: Correlation analyses showed that performance on the motor section of the Unified Huntington's Disease Rating Scale was significantly associated to scores on the Stroop-color word test and Cancellation task. Moreover, performance on the Total Functional Capacity and functional section of the Unified Huntington's Disease Rating Scale were significantly related to scores on the Trail making test. Last, score on the Frontal Behavioural Assessment was correlated with performance on the Stroop-color word test. Conclusions: Specific clinical features are associated to different types of attention in our HD patients. The severity of motor dysfunctions is strongly related to the ability to selectively pay attention on a target (selective attention) and to sustain it for extended time (sustained attention), whereas the decreasing of the functional abilities is associated to difficulties in paying attention on multiple tasks simultaneously (divided attention). Psychopathological signs are associated to the ability to direct the attention towards relevant stimuli by inhibiting the irrelevant ones (selective attention).